2019
DOI: 10.1088/1361-6668/ab17ec
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Rashba spin–orbit coupling, magnetization, and mixing of gap parameter on tunneling conductance in F∣NCSC junction of an F∣NCSC∣F spin valve

Abstract: In this paper, we study the quantum transport at the Ferromagnet|Noncentrosymmetric Superconductor (F|NCSC) interface of an F|S|F spin valve. In this context, we investigate the tunneling conductance and its dependence on Rashba Spin-Orbit Coupling (RSOC) considering different barrier strength and a significant Fermi Wave-vector Mismatch (FWM) at the ferromagnetic and superconducting regions. The study is carried out for different magnetization orientations and its strength. We developed Bogoliubov de Gennes (… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 113 publications
(214 reference statements)
0
14
0
Order By: Relevance
“…The last term in the first square backet of Eq. ( 5) is the contribution due to the RSOC, with V R being the strength of the RSOC and it arises due to the asymmetry of the interface as well as due to NCSC [58][59][60][61][62].…”
Section: Model and Formulationmentioning
confidence: 99%
See 2 more Smart Citations
“…The last term in the first square backet of Eq. ( 5) is the contribution due to the RSOC, with V R being the strength of the RSOC and it arises due to the asymmetry of the interface as well as due to NCSC [58][59][60][61][62].…”
Section: Model and Formulationmentioning
confidence: 99%
“…Since both even and odd frequency correlations are present in NCSC at the same time, so the gap matrix ∆αβ appearing in Eq. ( 2) can be represented as a superposition of the singlet and triplet components [60][61][62], i.e.…”
Section: Model and Formulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, in view of this the angularly averaged spin conductance can be written as [97,103,106,107,118]…”
Section: B Calculation Of Spin Conductance At the F|ncsc Interfacementioning
confidence: 99%
“…In most of the earlier works on tunnelling spectroscopy [97][98][99][100][101][102][103][104][105][106][107][108][109], it was found that the barrier thickness play a very significant role on the transport mechanism. However, the role of barrier thickness on spin transport is yet to be understood.…”
Section: A Spin Conductance Spectra At the F|ncsc Interfacementioning
confidence: 99%